Not-so-walking pneumonia: challenges in managing mycoplasma complicated by autoimmune hemolytic anemia in a young female - Bharadwaj, Sanket P.; Sharma, Rachit; Patel, Yatri S.; Shah, Dhruvi A.; Marwah, Aneeket T. (International Journal of Research in Medical Sciences, 2024)
Mycoplasma pneumoniae (Eaton agent) is a leading cause of atypical community-acquired pneumonia and can present with serious complications like acute respiratory distress syndrome (ARDS), acute respiratory failure and a variety of extrapulmonary manifestations including significant hemolysis. In this case report, we describe a case of a 17-year-old female with Mycoplasma pneumonia accompanied by major complications including hemolysis and possible macrolide resistance and explore the clinical obstacles faced in its diagnosis and treatment. The patient presented to the emergency room with a 10-day history of high-grade fever, coryza and dry cough with worsening dyspnea and palpitations since one day. Along with routine hematological and radiological workup, molecular and serological investigations confirmed the diagnosis. The patient was managed by a multidisciplinary team and had a prolonged hospital stay. She was primarily managed with antibiotics followed by glucocorticoids. She was discharged with oral prednisolone in tapering doses and showed a favorable recovery on follow-up. This case highlights the importance of including Mycoplasma in the differential diagnosis for a young adult with pneumonia and extrapulmonary manifestations especially in cases of non-responsiveness to conventional beta lactam therapy. Macrolide resistant M. pneumoniae strains have increasingly become prevalent in Asia. The case also emphasizes the significance of early diagnosis and prompt intervention to reduce complications and aid quick recovery.